2018
DOI: 10.4082/kjfm.17.0020
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Marital Status and Metabolic Syndrome in Korean Middle-Aged Women: The Sixth Korea National Health and Nutrition Examination Survey (2013–2014)

Abstract: BackgroundThis study aimed to investigate the relationship between marital status and the incidence of metabolic syndrome in Korean middle-aged women.MethodsBased on data from the sixth Korea National Health and Nutrition Examination Survey (2013–2014), 3,225 women aged 40–69 years were subjected to the analysis. Marital status was categorized as married, unmarried, separated, widowed, or divorced. The odds ratios (ORs) for metabolic syndrome were calculated based on marital status. After adjustment for age, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…This is attributed to the constellation of factors associated with the social events including buildup of stress, nutritional as well as lifestyle behavior like alcoholism, smoking to wade of stress resulting in MetS. These findings are consistent with several studies [64][65][66]. For example, it is hard for African men to adopt healthy behaviors such as cooking and eating healthy foods in their homes, but instead prefer restaurant prepared meals including processed/fast foods associated with MetS [9].…”
Section: Discussionsupporting
confidence: 85%
“…This is attributed to the constellation of factors associated with the social events including buildup of stress, nutritional as well as lifestyle behavior like alcoholism, smoking to wade of stress resulting in MetS. These findings are consistent with several studies [64][65][66]. For example, it is hard for African men to adopt healthy behaviors such as cooking and eating healthy foods in their homes, but instead prefer restaurant prepared meals including processed/fast foods associated with MetS [9].…”
Section: Discussionsupporting
confidence: 85%
“…Married male residents in the present seemed have lower incidence of MetS compared with non-married ones. This finding was consistence with the survey among Korean middle-aged women that prevalence of MetS was 30% in the married group and 34.2% in the unmarried group [27].And the possible explanation might be related to the low socioeconomic status among unmarried male in the present study. Those unmarried male were likely to be low income family (51.0% vs.11.9%, P < 0.001) and higher rate of low educational level (70.6% vs. 41.6%…”
Section: Discussionsupporting
confidence: 89%
“…One study revealed that sexually active women reported low total MRS scores and low somatic, psychological, and urogenital subscale scores [ 50 ]. In studies conducted on Koreans, it has been repeatedly reported that disease status (hypertriglyceridemia, metabolic syndrome, and depression) and health behaviors (smoking, binge drinking, and inadequate sleep) were significantly poor in middle-aged populations not living with partners [ 51 - 53 ], and our findings are consistent in this context. Meanwhile, there have been contradictory findings that married women complained more of vasomotor, genitourinary, or sexual symptoms than single/separated/widowed women [ 17 , 54 - 56 ].…”
Section: Discussionsupporting
confidence: 88%